Pembaharuan Kitab Hukum Dagang Indonesia : Antara Kodifikasi, Kompilasi dan Konsolidasi - Agus Budianto (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2013)
Renewal of the Wetboek van Koophandel (KUHD) is a Dutch colonial products a lot of problems. Although it has been stated in the National Legislation Program (Prolegnas) 2009 - 2014, but the number of regulations that have been removed from the KUHD, make arrangements of commercial law substance of overlapping, contradictory and theres a double substance. Therefore, to use renewal by the compilation method will be very ineffective, because when done harmonization, the many provisions that will be removed for united. When using the compilation method, will be in trouble to do the grouping of the material. Other methods are consolidated with Civil Code (KUHPerdata) Book III, to unify the principles and legal principles of legal trade into the agreements of law.